Social Media and the Spread of Global Terrorism and Criminal Activities: A Critical Review (Journal of Political Science and International Relationship, 2025)
This paper is a critical analysis of how social media can be used to intensify terrorism and organized crime from 2020 to 2025. Although the transformation of international communication and sociopolitical practices through digital platforms has proven to be influential, unregulated, and immediate, along with boundary issues, has created new breeding grounds for harmful use. Terrorist groups and criminal organizations (such as cartels, trafficking networks, and cybercrime gangs) utilize artificial intelligence, deepfake technology, encrypted communications, and newer alt-tech platforms to carry out recruitment, spread propaganda, organize activities, and secure financing. Recent incidents of fraud show that synthetic media is being used in terror finance scams, impersonation, and psychological operations as tools of psychological warfare, as well as bots built on AI to amplify narratives automatically. The paper consolidates empirical evidence on the psychological and social effects of repeated exposure to inhumane content, with a particular focus on youth, noting correlations with anxiety, polarization, distrust, and susceptibility to radicalization. It also examines the potential for online hate campaigns to escalate into real-world violence, which erodes public trust and weakens democratic institutions. The available countermeasures, such as algorithmic content moderation, rapid removal policies, and the development of international regulatory frameworks, are evaluated, and it is determined that their effectiveness is limited due to cross-jurisdictional enforcement challenges, civil liberties concerns, and the migration of hostile actors to less traceable territories. Based on interdisciplinary research and institutional reports, the review underscores the need for comprehensive, stewardship-oriented efforts that avoid fragmentation, apartheid-inspired policies, or rights violations. The recommended priority actions include implementing evidence-based measures, enhancing cross-border cooperation, and adopting ethical governance approaches to address the evolving cyber-physical landscape without compromising democratic rights.